The Probe Team [episode no. 309] (Quezon City Probe Productions, 1994)
The first part is an arguement between Church and State on the document presented at the International Conference on Population and Development in Cairo. The second part is about the recent study for the mentally ill not to be institutionalized. The last part is a play written in 1901 on fight against this Spanish colonizers.
Dumpy road to Cairo (18 min.) -- There's no place like home (12 min.) -- Walang sugat (20 min.)
Reporting, Luchi Cruz Valdes.
Keywords: Mentally ill -- Philippines; Philippines -- Population policy